2008
DOI: 10.1089/ten.tea.2007.0167
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Bone Regeneration by CCN2 Incorporated into Gelatin Hydrogel

Abstract: CCN family protein 2/connective tissue growth factor (CCN2/CTGF) is a unique molecule that promotes the entire endochondral ossification process and regeneration of damaged articular cartilage. Also, CCN2 has been shown to enhance the adhesion and migration of bone marrow stromal cells as well as the growth and differentiation of osteoblasts; hence, its utility in bone regeneration has been suggested. Here, we evaluated the effect of CCN2 on the regeneration of an intractable bone defect in a rat model. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…65 The osteogenic and bone regeneration capacity of collagen as a hydrogel substrate was superior to that of fibrin glue and alginate 66 and modifying collagen hydrogels by loading them with connective tissue growth factor (CTGF) could enhance osteogenic differentiation even further. 67 Here, we determined the effect of bFGF on osteogenic differentiation of MSCs in collagen hydrogels. bFGF is a good candidate because we previously found that osteogenic phenotype acquisition of preosteoblastic MC3T3-E1 cells grown on hydroxyapatite bone granules was much greater in the presence of bFGF than without.…”
mentioning
confidence: 99%
“…65 The osteogenic and bone regeneration capacity of collagen as a hydrogel substrate was superior to that of fibrin glue and alginate 66 and modifying collagen hydrogels by loading them with connective tissue growth factor (CTGF) could enhance osteogenic differentiation even further. 67 Here, we determined the effect of bFGF on osteogenic differentiation of MSCs in collagen hydrogels. bFGF is a good candidate because we previously found that osteogenic phenotype acquisition of preosteoblastic MC3T3-E1 cells grown on hydroxyapatite bone granules was much greater in the presence of bFGF than without.…”
mentioning
confidence: 99%
“…Since CCN2 acts on both types of the cells positively, this factor may be coordinating efficient and balanced bone remodeling. This functional property of CCN2 is well demonstrated by the regenerative effect of CCN2 on bone defects [13]. The fact that mechanical stimuli induce CCN2 production by osteocytes also indicates the property of CCN2 as a coordinator of bone remodeling [44].…”
Section: Ccn2 and Tooth Developmentmentioning
confidence: 88%
“…By mimicking this process, we are able to accelerate the regeneration of intractable bone defects. In a rat model, application of CCN2 adsorbed onto gelatin hydrogel for durable and gradual release efficiently accelerated the regeneration of intractable bone defects [13]. This is not of a great impact per se; for other factors, such as BMP-2 and FGF-2, have been indicated to be useful in promoting bone repair.…”
Section: Bone Regeneration By Ccn2mentioning
confidence: 98%
See 2 more Smart Citations